Electro‐Reconfigurable Adaptive Microlens with Simultaneous Multidirectional Focal Adjustment and Zooming. Issue 8 (20th March 2023) - Yoon, Jae Uk; Han, Dong‐Heon; Oh, Seung‐Ju; Woo, Insun; Park, Hyeon‐Su; Bae, Jin Woo
Abstract: Electrically reconfigurable lenses capable of focal adjustment and zooming require deformable adaptive optical components. However, existing electroactive optical devices that perform these functions are limited by fluid leakage or require complex mechanical parts. Although polyvinyl chloride (PVC) gel‐based lenses with variable focal lengths and zooming have recently been developed, focal adjustment can only be made in the horizontal axis. Herein, a PVC gel‐based adaptive microlens capable of controlling the focal length and focal point simultaneously in the vertical, horizontal, and diagonal directions without mechanical gears or liquid leakage is presented. By optimizing the characteristics of PVC gels plasticized with three different structured plasticizers, a PVC gel‐based adaptive microlens is fabricated. The produced microlens demonstrates the properties of multidirectional focal adjustment, variable focal length (+33.7 to −15.1 mm) at low input voltages (<300 V), excellent transparency (>90%), fast response (0.10 s at 100 V), silent operation, low power consumption (0.39 mW), and excellent potential for further miniaturization. Abstract : A polyvinyl chloride gel‐based electro‐reconfigurable adaptive microlens with simultaneous multidirectional focal adjustment and zooming is presented. The proposed microlens shows vertical, horizontal, and diagonal focal adjustment, variable focal length (+33.7 to −15.1 mm) at low input voltages (<300 V), excellent transparency (>90%), fast response (0.10 s), silent operation, low power consumption (0.39 mW), and excellent potential for future optical modules.